Pola Komunikasi Komunitas dalam Mempertahankan Kohesivitas Kelompok KZOI Region Banten - Vanie, Adevy; Leasfita, Ade (CV. ITTC INDONESIA, 2025)
The KZOI Region Banten community has survived for a decade and even some KZOI Region Banten members even though they have changed the type, brand and CC of the motorbike remain members. The purpose of this research is to find out the communication patterns of the Community in maintaining the cohesiveness of the KZOI Region Banten group. This research method uses descriptive with a qualitative approach as well as non-participant observation and interviews with eight members of the KZOI Region Banten community. The result of this research is that the communication pattern used by the KZOI Region Banten community is an all-channel pattern or star pattern. This can be seen when all members have equal rights in providing ideas or ideas for touring, rolling, sunday morning (sunmori) and events, not requiring and forcing all members to attend meetings (kopdar), giving freedom without strict rules but still following applicable norms so that from all of that a sense of belonging, comfort, kinship, togetherness to harmonisation between fellow members is created. Keywords: Communication Patterns, Group Cohesiveness, KZOI Banten